N-alkane isomerization catalyst prepared from polyaluminum chloride

By using polymer catalysts, especially those supported on platinum, yttrium, and polyaluminum chloride, the shortcomings of existing catalysts have been overcome, and efficient isomerization of light n-alkanes has been achieved, particularly with a significant increase in the isomerization rate of C5 and C6 alkanes.

CN119303600APending Publication Date: 2025-01-14REZEL CATALYSTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411366051.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-16
Filing Date
2024-09-29
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing light n-alkane isomerization catalysts have shortcomings in terms of strict requirements for water and sulfur content, strong equipment corrosion, poor thermal stability, and low octane number of isomer products, making it difficult to effectively improve the isomerization rate of C4, C5, and C6 n-alkanes.

Method used

Polymer catalysts with special structures, including alumina or zirconium oxide as supports, are prepared by loading platinum, yttrium and polyaluminum chloride through specific processes to improve the isomerization performance of the catalysts.

Benefits of technology

It significantly improves the isomerization rate of light n-alkanes, especially the isomerization rate of C5 and C6 n-alkanes by 30-40%, and maintains high catalytic activity at lower reaction temperatures and pressures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005066252700000041
    Figure BDA0005066252700000041
  • Figure BDA0005066252700000081
    Figure BDA0005066252700000081
  • Figure BDA0005066252700000082
    Figure BDA0005066252700000082
Patent Text Reader

Abstract

The invention provides an isomerization catalyst for light n-alkanes. Polyaluminum chloride is used in the isomerization catalyst. The isomerization performance of the catalyst can be improved, and the catalyst is especially suitable for isomerization reaction of C4, C5 and C6 n-alkanes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of petrochemical catalysts. Background Art

[0002] The main processes for producing clean gasoline include alkylation, catalytic cracking, reforming, and adding MTBE. Among them, alkane isomerization, as one of the important reactions for the comprehensive utilization of low-carbon alkanes, is one of the most effective methods for producing high-octane gasoline. Nowadays, with the increase in crude oil processing, a large amount of C4 by-products are produced, and C5 and C6 alkane fractions also increase. Among them, n-butane is cheap and has low economic benefits as a fuel or refrigerant. N-pentane and n-hexane will reduce the octane number of reformed oil. Therefore, the most economically efficient means at present is to convert the products of C4, C5, and C6 normal alkanes into high-octane gasoline additive components through isomerization reactions.

[0003] Currently, the isomerization catalysts for light normal alkanes such as n-butane, n-pentane, and n-hexane sold on the market mainly include three categories: metal-loaded chlorinated alumina, metal-loaded sulfated zirconium oxide, and metal-loaded molecular sieves.

[0004] The isomerization catalyst of metal-loaded chlorinated alumina usually adopts a platinum halide / alumina catalyst with γ-Al2O3 as a carrier. During the operation, an appropriate amount of chloride additive needs to be continuously added to the raw material. The main problem of this technology is that it has strict requirements on the water and sulfur content in the raw material, which needs to be less than 0.1ppm. At the same time, the chlorine-containing substances generated during the reaction are corrosive to the equipment, increasing the equipment material cost and maintenance cost, and also polluting the environment.

[0005] The isomerization catalyst of metal-loaded sulfated zirconium oxide, patent CN1660973A discloses a method for isomerization of C5 and C6 alkanes, the catalyst preparation process includes: preparing zirconium hydroxide by reacting zirconium salt solution with alkaline solution; mixing zirconium hydroxide with silica sol and drying; containing SO4 2- Solution impregnation and drying; metal salt solution impregnation, drying and calcination. Among them, the metal-loaded sulfated zirconium oxide catalyst has strong acidity, high reaction activity, strong anti-toxicity, and low requirements on the water content and oxide content in the raw materials, but its thermal stability is poor.

[0006] Metal-loaded molecular sieve isomerization catalysts, USP4232181 and USP4665272 patents introduce methods for preparing metal-loaded molecular sieve isomerization catalysts, but since the molecular sieve isomerization catalyst is a zeolite-type bifunctional catalyst, the actual application temperature of the catalyst is relatively high, and the equilibrium concentration of the isomerized product is low at high temperature, which directly leads to a low octane number of the isomerized product.

[0007] Finding new catalysts that are more effective in promoting the isomerization of light normal alkanes is a common research direction in this field. Summary of the invention

[0008] Combining the advantages and disadvantages of the above catalysts, the present invention uses a polymer with a special structure to prepare an isomerization catalyst, improves the isomerization performance of the catalyst, and is particularly suitable for the isomerization reaction of C4, C5, and C6 normal alkanes. Specifically, the present invention provides an isomerization catalyst for light normal alkanes, characterized in that it includes a carrier, aluminum oxide or zirconium oxide loaded in the carrier, platinum, yttrium, and polyaluminum chloride, wherein the mass percentage of platinum is 0.2-0.4%, the mass percentage of yttrium is 0.2-0.4%, the mass percentage of chlorine is 2-6%, and the specific surface area is 180-230m 2 / g, strength is 80~110N / cm.

[0009] The present invention applies polyaluminium chloride to the isomerization catalysis of light normal alkanes for the first time. Experimental comparison shows that the catalyst finally treated with polyaluminium chloride has a significantly improved isomerization effect of more than 20% on light normal alkanes, especially the isomerization rate of C5 and C6 normal alkanes reaches 30-40%, indicating that the catalyst of the present invention is more suitable for the isomerization catalysis of C5 and C6 normal alkanes, especially C6.

[0010] The present invention also provides a method for preparing a catalyst for isomerization of light normal alkanes, which comprises the following contents:

[0011] (1) kneading, extruding, and calcining at 450-600° C. 500-1000 parts by weight of an aluminum oxide precursor or / and a zirconium oxide precursor, 100-200 parts by weight of an aluminum salt or / and a zirconium salt, and 30-50 parts by weight of an organic polymer material with 150-300 parts by weight of a 30-40% nitric acid aqueous solution to obtain a catalyst carrier;

[0012] (2) attaching 0.1 to 1.0 parts by weight of a soluble platinum salt and 1.0 to 5.0 parts by weight of a yttrium salt to a catalyst carrier, wherein the mass ratio of the platinum salt to the catalyst carrier is 0.1 to 1:100, and the mass ratio of the yttrium salt to the catalyst carrier is 2.5 to 4:100; calcining at 450 to 550° C. to obtain an intermediate;

[0013] (3) placing the intermediate in 100-500 parts by weight of a polyaluminium chloride aqueous solution, with polyaluminium chloride: water = 1:8-15; immersing, and drying to obtain a catalyst.

[0014] γ-Al2O3 has the characteristics of large specific surface area, good adsorption performance, and good surface acidity. It is a widely used activated alumina and can be used as a catalyst and catalyst carrier in petrochemical industry.

[0015] In the present invention, the alumina precursor is preferably selected from hydrated alumina, including pseudo-boehmite and boehmite.

[0016] Boehmite, also known as monohydrate soft aluminum stone, boehmite, etc., has the molecular formula of γ-AlOOH. It is an important precursor of activated alumina. It is an activated alumina precursor with high order and complete crystallization, and therefore has better stability than pseudo-boehmite.

[0017] Pseudoboehmite is a kind of incompletely crystallized monohydrated aluminum oxide with a chemical composition similar to that of boehmite. It contains 1.25 to 2.0 crystal waters and is a type of incompletely crystallized hydrated aluminum oxide, also known as monohydrated aluminum oxide and pseudo-boehmite. It has a layered structure and a high specific surface area. Pseudoboehmite can be converted into aluminum oxide under high temperature calcination. It is a precursor of aluminum oxide and maintains a high specific surface area and pore structure, which is conducive to the dispersion of active components and the catalytic reaction. Pseudoboehmite as a binder helps to shape the carrier and enhance the mechanical strength of the catalyst during the catalyst preparation process. This is crucial for the stability and durability of the catalyst in practical applications. An appropriate amount of pseudoboehmite as a binder can also affect the catalytic performance of the resulting catalyst. For example, studies have shown that when preparing a catalyst for the skeletal isomerization of n-butene to isobutylene, adding an appropriate amount of pseudoboehmite as a binder can increase the n-butene conversion rate and isobutylene yield.

[0018] In the present invention, the zirconium oxide precursor includes zirconium oxysulfate, zirconium oxychloride, zirconium nitrate, and zirconium oxyoxalate.

[0019] Zirconia has good chemical stability, and its surface has both acidity and alkalinity and redox properties. This surface property makes zirconium oxide an effective catalyst carrier, promoting the adsorption and activation of normal alkane molecules on the catalyst surface. Especially after sulfate treatment, SO4 2- / ZrO2, its acidity is significantly enhanced, which is conducive to the isomerization reaction. Zirconium oxides of different crystal phases (such as tetragonal phase, monoclinic phase, etc.) show different catalytic performance in the catalytic reaction, and the catalyst loaded with tetragonal ZrO2 shows higher n-alkane conversion activity.

[0020] Wherein, the aluminum salt includes one or more of polyaluminum chloride, tetrahydroxyaluminum, aluminum sol, aluminum trichloride, and aluminum sulfate. By adding aluminum salt, more active sites are introduced on the γ-Al2O3 carrier, thereby improving the overall activity of the catalyst. It is not easy to add too much aluminum salt. Too much addition may cause crowding of active sites, pore blockage, etc., thereby causing the catalyst performance to decline. Therefore, it is necessary to strictly control the amount of aluminum added within a reasonable range.

[0021] The zirconium salt includes one or more of zirconium tetrachlorohydroxide, zirconium oxysulfate, zirconium nitrate, and zirconium oxychloride. The isomerization reaction of normal alkanes can only occur in the presence of a strong acid catalyst. The superacid prepared by zirconium oxide loaded with sulfate is also suitable for catalyzing the isomerization reaction of alkanes. Zirconium can be used as an auxiliary agent in combination with Al2O3 to form a composite catalyst. This composite catalyst shows higher catalytic activity and stability when catalyzing the isomerization of light normal alkanes.

[0022] Wherein, the organic polymer material includes one or more of methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, polyvinyl alcohol and polyethylene glycol.

[0023] Organic polymer materials play multiple roles in the preparation of alumina catalyst carriers, such as molding aids, adhesives, pore structure regulation and stability improvement. These roles jointly promote the optimization and improvement of catalyst carrier performance. As a molding aid, it is mainly filled in the gaps of the molded object, which helps to improve the bonding strength between particles, making the catalyst carrier easier to shape and maintain a stable structure during the preparation process, which is crucial for the subsequent catalyst loading and catalytic reaction process. It has certain adhesive properties, which can enhance the binding force of the internal components of the catalyst, so that the carrier materials are more closely combined; this close combination helps to improve the mechanical strength and thermal stability of the catalyst carrier, and prevent it from breaking or falling off during subsequent high-temperature roasting and use. By adding an appropriate amount of organic polymer materials, during the roasting process, as it decomposes and disappears, the macroporous structure of the alumina carrier can be appropriately expanded, thereby changing the pore distribution characteristics of the carrier. In addition, the presence of organic polymer materials may also slow down the growth rate of alumina grains during roasting to a certain extent, thereby maintaining a high specific surface area and catalytic activity.

[0024] Wherein, the soluble platinum salt includes one or more of chloroplatinic acid, platinum sulfate, and platinum nitrate. Platinum, as a precious metal catalyst, is an important active center for the isomerization reaction of light normal alkanes. Platinum catalysts can effectively promote the activation, dehydrogenation, isomerization and hydrogenation steps of alkane molecules, thereby realizing the isomerization conversion of alkanes. Among them, chloroplatinic acid has a high catalytic activity, can significantly increase the reaction rate in the isomerization reaction of normal alkanes, and enable the reaction to reach the desired conversion rate in a shorter time; in addition, chloroplatinic acid can increase the chlorine loading in the catalyst, and a high chlorine loading helps to enhance the acidity of the catalyst, thereby promoting the isomerization reaction.

[0025] Wherein, the soluble yttrium salt includes one or more of yttrium nitrate, yttrium chloride, and yttrium oxalate. The introduction of yttrium can enhance the stability of the catalyst and reduce the deactivation of the catalyst during the reaction. This may be because yttrium forms a stable compound or structure with other components in the catalyst, thereby improving the catalyst's ability to resist carbon deposition and poisoning.

[0026] The present invention also provides a method for isomerizing light normal alkanes, and the catalyst is used for the isomerization reaction of light normal alkanes.

[0027] Furthermore, the light normal alkane is selected from one or more of n-butane, n-pentane and n-hexane.

[0028] Polyaluminium chloride, also known as polyaluminium chloride (PAC), composite polyaluminium chloride, basic aluminium chloride, is a water-soluble inorganic high molecular polymer between AlCl3 and Al(OH)3, with the molecular formula: [Al2(OH) n Cl 6-n ·xH2O] m (m≤10, n=1~5), it is a highly charged polymerized ring chain, has a high degree of electrical neutralization and bridging effect on colloids and particles in water, and can strongly remove micro-toxic substances and heavy metal ions, with stable properties. This product is tested according to GB15892-2003 standard and meets the relevant regulations:

[0029] Table 1 GB15892-2003 indicators

[0030]

[0031] The basic component that causes polyaluminium chloride to have various forms is OH ions. The index for measuring OH ions in polyaluminium chloride is called basicity (abbreviated as B). Basicity is usually defined as the equivalent percentage of OH and Al in polyaluminium chloride molecules (〔OH〕 / 〔Al〕×100(%)).

[0032] The basicity of polyaluminium chloride is a relatively important index in polyaluminium. The basicity of the polyaluminium chloride product used in the present invention is generally controlled at 50-55%, and the alumina content is 28-30%.

[0033] In certain embodiments of the present invention, the basicity of the polyaluminum chloride product is selected from 51%; in certain embodiments of the present invention, the basicity of the polyaluminum chloride product is selected from 52%; in certain embodiments of the present invention, the basicity of the polyaluminum chloride product is selected from 53%; in certain embodiments of the present invention, the basicity of the polyaluminum chloride product is selected from 54%; in certain embodiments of the present invention, the basicity of the polyaluminum chloride product is selected from 55%.

[0034] In some embodiments of the present invention, the aluminum oxide content is 28%; in some embodiments of the present invention, the aluminum oxide content is 29%; in some embodiments of the present invention, the aluminum oxide content is 30%.

[0035] Polyaluminium chloride, due to its strong bridging adsorption, is currently often used as a highly efficient inorganic polymer flocculant. During the hydrolysis process, it undergoes physical and chemical changes such as electrochemistry, coagulation, adsorption and precipitation, and is widely used in wastewater treatment. In addition, some people currently use it as a catalyst for the synthesis of heterocyclic compounds.

[0036] In certain embodiments of the present invention, the mass ratio of the platinum salt to the catalyst carrier is 0.6-0.7:100, and the mass ratio of the yttrium salt to the catalyst carrier is 3.0-3.5:100.

[0037] In the present invention, the concentration and dosage of polyaluminium chloride are significantly correlated with the final catalytic effect. In some specific embodiments of the present invention, the best isomerization catalytic effect can be achieved only at a specific concentration and dosage. For example, in the polyaluminium chloride aqueous solution, the weight ratio of polyaluminium chloride to water is 1:10-12, and the volume of the polyaluminium chloride aqueous solution is substantially equal to the volume of the catalyst intermediate. In certain embodiments of the present invention, the weight ratio of polyaluminium chloride to water is 1:10. In certain embodiments of the present invention, the weight ratio of polyaluminium chloride to water is 1:11. In certain embodiments of the present invention, the weight ratio of polyaluminium chloride to water is 1:12.

[0038] Soluble platinum salt and yttrium salt are attached to the catalyst support in the form of a solution, and are further an aqueous solution. In certain embodiments of the present invention, the concentration of the aqueous solution of the soluble platinum salt can be selected from 0.005 to 0.03 mmol / ml, and the concentration of the aqueous solution of the soluble yttrium salt can be selected from 0.05 to 0.1 mmol / ml. In certain embodiments of the present invention, the concentration of the aqueous solution of the soluble platinum salt can be selected from 0.005 to 0.02 mmol / ml, and the concentration of the aqueous solution of the soluble yttrium salt can be selected from 0.05 to 0.09 mmol / ml. In certain embodiments of the present invention, the concentration of the aqueous solution of the soluble platinum salt can be selected from 0.01 mmol / ml, and the concentration of the aqueous solution of the soluble yttrium salt can be selected from 0.07 mmol / ml.

[0039] The drying time of the present invention can be reasonably selected according to the drying temperature, the amount of material and the type of drying equipment, so that the moisture content of the dried material does not affect the subsequent roasting. Under preferred conditions, the drying temperature is 65-140°C, for example, it can be 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C or any value in the range of any two of the above values, preferably 80-110°C; the drying time is 4-18h, for example, it can be 4 h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, 15h, 15.5h, 16h, 16.5h, 17h, 17.5h, 18h or any value in the range consisting of any two of the above numerical values.

[0040] In the present invention, the calcination temperature can be 450°C, 500°C, 525°C, 550°C, 600°C or any value in the range of any two of the above values; the calcination time can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 7h, 8h, 9h, 9.5h, 10h, 10.5h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h or any value in the range of any two of the above values, for example, 3 to 10h, preferably 4 to 8h.

[0041] In certain embodiments of the present invention, the catalyst obtained by the following method may be preferably used:

[0042] 1000 parts of pseudo-boehmite, 100 parts of polyaluminium chloride, 30 parts of methyl cellulose and 300 parts of 35% nitric acid aqueous solution are kneaded, extruded into a strip carrier, dried and calcined at 550°C to obtain a catalyst carrier;

[0043] 0.63 parts of chloroplatinic acid and 3.09 parts of yttrium nitrate are dissolved in 150 parts of water, and 98.7 parts of the catalyst carrier are impregnated therein, dried, and calcined at 500° C. The calcined catalyst intermediate is then placed in a polyaluminum chloride aqueous solution (polyaluminum chloride: water = 1:12), impregnated, and dried to obtain the catalyst of the present invention.

[0044] In certain embodiments of the present invention, a catalyst obtained by the following method may be used:

[0045] 500 parts of pseudo-boehmite, 500 parts of zirconyl sulfate, 100 parts of aluminum zirconium tetrachlorohydrate, 50 parts of methyl cellulose, and 200 parts of a 35% nitric acid aqueous solution are kneaded, extruded into a strip carrier, dried, and calcined at 550° C. to obtain a catalyst carrier;

[0046] 0.63 parts of chloroplatinic acid and 3.09 parts of yttrium nitrate are dissolved in 150g of water, 98.7 parts of the carrier are impregnated therein, dried, and calcined at 500°C. The calcined catalyst intermediate is placed in a polyaluminum chloride aqueous solution (polyaluminum chloride: water = 1:10), impregnated, and dried to obtain a catalyst.

[0047] By using the catalyst of the present invention, the catalytic reaction temperature can be relatively low, and the reaction conditions can be: pressure 2-3 MPa, temperature 170-200°C.

[0048] In certain embodiments of the present invention, the pressure is 2.0 MPa; in certain embodiments of the present invention, the pressure is 2.1 MPa; in certain embodiments of the present invention, the pressure is 2.2 MPa; in certain embodiments of the present invention, the pressure is 2.3 MPa; in certain embodiments of the present invention, the pressure is 2.4 MPa; in certain embodiments of the present invention, the pressure is 2.5 MPa; in certain embodiments of the present invention, the pressure is 2.6 MPa; in certain embodiments of the present invention, the pressure is 2.7 MPa; in certain embodiments of the present invention, the pressure is 2.8 MPa; in certain embodiments of the present invention, the pressure is 2.9 MPa; in certain embodiments of the present invention, the pressure is 3.0 MPa.

[0049] In certain embodiments of the present invention, the temperature is 170°C; in certain embodiments of the present invention, the temperature is 175°C; in certain embodiments of the present invention, the temperature is 180°C; in certain embodiments of the present invention, the temperature is 185°C; in certain embodiments of the present invention, the temperature is 190°C; in certain embodiments of the present invention, the temperature is 195°C; in certain embodiments of the present invention, the temperature is 200°C. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment and effect test.It should be understood that the specific embodiments and effect test described herein are only used to explain the present invention and are not intended to limit the present invention.In addition, if not clearly stated, all reagents adopted in the following embodiments are all commercially available, or can be synthesized according to this article or known methods, and for the reaction conditions not listed, they are also easily obtained by those skilled in the art.

[0051] The polyaluminium chloride used in the present invention is purchased from a commercial product and complies with the GB15892-2003 standard. The molecular formula is: [Al2(OH)n Cl 6-n ·xH2O] m (m≤10, n=1~5), basicity is 52%, and alumina content is 29%.

[0052] Example 1

[0053] Preparation of vector:

[0054] 1000g of pseudo-boehmite, 100g of polyaluminium chloride and 30g of methyl cellulose were added to a kneader in sequence for 20 to 50min of kneading. 300g of 35% nitric acid aqueous solution was added and kneading was continued for 20 to 40min. The kneaded clinker was put into an extruder for extrusion. The extruded strip carrier was dried at 100°C for 8 hours and then calcined at 550°C for 8 hours to obtain a catalyst carrier 1 with a specific surface area of ​​220m 2 / g, strength 80N / cm.

[0055] Preparation of catalyst:

[0056] 98.7g of carrier 1 was placed in a rotary evaporation bottle, and vacuumed for 2h. 0.63g of 0.0015 (0.01mmol / ml) of chloroplatinic acid and 3.09g of 0.011 (0.07mmol / ml) of yttrium nitrate were dissolved in 150g of water to prepare a solution. The solution was impregnated into the rotary evaporation bottle with the carrier, and rotated at 2r / min for 30min. The excess water was evaporated by vacuuming. After the surface of the carrier was dried, it was taken out, and then dried at 80℃ for 6 hours, and calcined at 500℃ for 4 hours. The calcined catalyst intermediate was placed in a polyaluminum chloride aqueous solution (1:12), and impregnated by the method of impregnating equal volume (volume of intermediate = volume of polyaluminum chloride aqueous solution), and purged at 250℃ for 4 hours under a nitrogen atmosphere to obtain catalyst A.

[0057] Example 2

[0058] Preparation of vector:

[0059] 1000g of pseudo-boehmite, 100g of aluminum zirconium tetrachlorohydrate, and 30g of methyl cellulose were added to a kneader in sequence for 20 to 50min, and 300g of a 35% nitric acid aqueous solution was added and kneaded for 20 to 40min. The kneaded clinker was put into an extruder for extrusion, and the extruded strip carrier was dried at 100°C for 8 hours, and then calcined at 550°C for 8 hours to obtain a catalyst carrier 2 with a specific surface area of ​​218m 2 / g, strength 96N / cm.

[0060] Preparation of catalyst:

[0061] 98.7g of carrier 2 was placed in a rotary evaporation bottle, and vacuumed for 2h. 0.63g of chloroplatinic acid and 3.09g of yttrium nitrate were dissolved in 150g of water to prepare a solution. The solution was impregnated into the rotary evaporation bottle with the carrier, and rotated at 2r / min for 30min. The excess water was evaporated by vacuuming. After the surface of the carrier was dried, it was taken out, and then dried at 80℃ for 6 hours, and calcined at 500℃ for 4 hours. The calcined catalyst intermediate was placed in a 1:12 polyaluminum chloride aqueous solution, and impregnated by the method of impregnating equal volume (intermediate volume = polyaluminum chloride aqueous solution volume), and purged at 250℃ for 4 hours under a nitrogen atmosphere to obtain catalyst B.

[0062] Example 3

[0063] Preparation of vector:

[0064] 1000g of pseudo-boehmite, 100g of tetrahydroxyaluminum, and 30g of methyl cellulose were added to a kneader in sequence for 20 to 50min of kneading. 300g of 35% nitric acid aqueous solution was added and kneading was continued for 20 to 40min. The kneaded clinker was put into an extruder for extrusion. The extruded strip carrier was dried at 100°C for 8 hours and then calcined at 550°C for 8 hours to obtain a catalyst carrier 3 with a specific surface area of ​​208m 2 / g, strength 92N / cm.

[0065] Preparation of catalyst:

[0066] 98.7g of carrier 3 was placed in a rotary evaporation bottle, and vacuumed for 2h. 0.63g of chloroplatinic acid and 3.09g of yttrium nitrate were dissolved in 150g of water to prepare a solution. The solution was impregnated into the rotary evaporation bottle with the carrier, and rotated at 2r / min for 30min. The excess water was evaporated by vacuuming. After the surface of the carrier was dried, it was taken out, and then dried at 80℃ for 6 hours, and roasted at 500℃ for 4 hours. The calcined catalyst intermediate was placed in a 1:12 polyaluminum chloride aqueous solution, and impregnated by the method of impregnating equal volume (intermediate volume = polyaluminum chloride aqueous solution volume), and purged at 250℃ for 4 hours under a nitrogen atmosphere to obtain catalyst C.

[0067] Example 4

[0068] Preparation of vector:

[0069] 500g of pseudo-boehmite, 500g of zirconium sulfate, 100g of aluminum zirconium tetrachlorohydrate, and 50g of methyl cellulose were added to a kneader in sequence for 20 to 50min, and 200g of a 35% nitric acid aqueous solution was added and kneaded for 20 to 40min. The kneaded clinker was put into an extruder for extrusion, and the extruded strip carrier was dried at 100°C for 8 hours, and then calcined at 550°C for 8 hours to obtain a catalyst carrier 4 with a specific surface area of ​​189m 2 / g, strength 99N / cm.

[0070] Preparation of catalyst:

[0071] 98.7g of carrier 4 was placed in a rotary evaporation bottle, and vacuumed for 2h. 0.63g of chloroplatinic acid and 3.09g of yttrium nitrate were dissolved in 150g of water to prepare a solution. The solution was impregnated into the rotary evaporation bottle with the carrier, and rotated at 2r / min for 30min. The excess water was evaporated by vacuuming. After the surface of the carrier was dried, it was taken out, and then dried at 80°C for 6 hours, and calcined at 500°C for 4 hours. The calcined catalyst intermediate was placed in a 1:10 polyaluminum chloride aqueous solution, and impregnated by the method of impregnating equal volume (intermediate volume = polyaluminum chloride aqueous solution volume), and purged at 250°C for 4 hours under a nitrogen atmosphere to obtain catalyst D.

[0072] Example 5

[0073] Preparation of vector:

[0074] 1000g zirconium sulfate, 100g pseudo-boehmite, 100g aluminum zirconium tetrachlorohydrate, and 50g methyl cellulose were added to a kneader in sequence for 20 to 50 minutes. 180g 35% nitric acid aqueous solution was added and kneaded for 20 to 40 minutes. The kneaded clinker was put into an extruder for extrusion. The extruded strip carrier was dried at 100°C for 8 hours and then calcined at 550°C for 8 hours to obtain a catalyst carrier 5 with a specific surface area of ​​180m 2 / g, strength 102N / cm.

[0075] Preparation of catalyst:

[0076] 98.7g of carrier 4 was placed in a rotary evaporation bottle, and vacuumed for 2h. 0.63g of chloroplatinic acid and 3.09g of yttrium nitrate were dissolved in 150g of water to prepare a solution. The solution was impregnated into the rotary evaporation bottle with the carrier, and rotated at 2r / min for 30min. The excess water was evaporated by vacuuming. After the surface of the carrier was dried, it was taken out, and then dried at 80°C for 6 hours, and calcined at 500°C for 4 hours. The calcined catalyst intermediate was placed in a 1:10 polyaluminum chloride aqueous solution, and impregnated by the method of impregnating equal volume (intermediate volume = polyaluminum chloride aqueous solution volume), and purged at 250°C for 4 hours under a nitrogen atmosphere to obtain catalyst E.

[0077] Comparative Example 1:

[0078] Preparation of vector:

[0079] 1000g of pseudo-boehmite, 100g of polyaluminium chloride and 30g of methyl cellulose were added to a kneader in sequence for 20 to 50min of kneading. 300g of 35% nitric acid aqueous solution was added and kneading was continued for 20 to 40min. The kneaded clinker was put into an extruder for extrusion. The extruded strip carrier was dried at 100°C for 8 hours and then calcined at 550°C for 8 hours to obtain a catalyst carrier 1 with a specific surface area of ​​220m 2 / g, strength 80N / cm.

[0080] Preparation of catalyst:

[0081] 98.7g of carrier 1 was placed in a rotary evaporation bottle, and vacuumed for 2 hours. 0.63g of chloroplatinic acid and 3.09g of yttrium nitrate were dissolved in 150g of water to prepare a solution. The solution was impregnated into the rotary evaporation bottle with the carrier, and rotated at 2r / min for 30 minutes. The excess water was evaporated by vacuuming. After the surface of the carrier was dried, it was taken out, and then dried at 80°C for 6 hours and calcined at 500°C for 4 hours. The catalyst intermediate was reacted in an HCl atmosphere at a reaction temperature of 250°C and a reaction time of 4 hours. Comparative agent 1 was obtained.

[0082] Comparative Example 2:

[0083] Preparation of vector:

[0084] 1000g zirconium sulfate, 100g pseudo-boehmite, 100g aluminum zirconium tetrachlorohydrate, and 50g methyl cellulose were added to a kneader in sequence for 20 to 50 minutes. 180g 35% nitric acid aqueous solution was added and kneaded for 20 to 40 minutes. The kneaded clinker was put into an extruder for extrusion. The extruded strip carrier was dried at 100°C for 8 hours and then calcined at 550°C for 8 hours to obtain a catalyst carrier 5 with a specific surface area of ​​180m2 / g, strength 102N / cm.

[0085] Preparation of catalyst:

[0086] 98.7 g of carrier 4 was placed in a rotary evaporation bottle, and vacuumed for 2 hours. 0.63 g of chloroplatinic acid and 3.09 g of yttrium nitrate were dissolved in 150 g of water to prepare a solution. The solution was immersed in the rotary evaporation bottle with the carrier, rotated at 2 r / min for 30 minutes, and vacuumed to evaporate excess water. When the surface of the carrier was dry, it was taken out, and then dried at 80° C. for 6 hours, and calcined at 500° C. for 4 hours. Contrast agent 2 was obtained.

[0087] The physicochemical indicators of the catalyst are shown in Table 1, and the isomerization performance test data of the catalyst are shown in Table 2.

[0088] Table 1

[0089]

[0090] The isomerization catalyst obtained in the examples and comparative examples was used in a fixed bed reactor. The catalyst size was 20-40 mesh, the filling volume was 5 mL, the reaction pressure was 2.5 MPa, the temperature was 180° C., and the mass space velocity was 1.5 h -1 , hydrogen-to-oil molar ratio: 2.0, raw material composition: n-butane: 25%, n-pentane: 25%, n-hexane: 25%, nitrogen: balance.

[0091] Table 2

[0092]

[0093]

[0094] Compared with comparative examples 1 and 2, the isomerization rate of C4 to C6 by the catalyst of the present invention is increased by about 20%, 30% and 40%, respectively. It can be seen that the catalyst treated with polyaluminium chloride in the present invention can effectively increase the isomerization rate of light normal alkanes, and has a more significant catalytic effect on C5 and C6, especially on C6.

[0095] Through a comprehensive comparison of the isomerization green of C4-C6 normal alkanes, it can be seen that the comprehensive catalytic effect of the catalyst A of the present invention is the best, followed by the catalyst D.

[0096] In addition, the present invention knows that the isomerization rate can be improved after loading chlorine, and the catalyst intermediate is also loaded with chlorine by gaseous HCl deposition in Comparative Example 1. However, by comparison, it can be seen that in the embodiment of the present invention, after the final impregnation treatment with polyaluminum chloride aqueous solution, the catalytic effect is significantly better than the traditional chlorine loading treatment method.

Claims

1. A method for preparing a catalyst for isomerization of light normal alkanes, characterized in that: It includes the following: (1) kneading, extruding, and calcining at 450-600° C. 500-1000 parts by weight of an aluminum oxide precursor or / and a zirconium oxide precursor, 100-200 parts by weight of an aluminum salt or / and a zirconium salt, and 30-50 parts by weight of an organic polymer material with 150-300 parts by weight of a 30-40% nitric acid aqueous solution to obtain a catalyst carrier; (2) attaching 0.1 to 1.0 parts by weight of a soluble platinum salt and 1.0 to 5.0 parts by weight of a yttrium salt to a catalyst carrier, wherein the mass ratio of the platinum salt to the catalyst carrier is 0.1 to 1:100, and the mass ratio of the yttrium salt to the catalyst carrier is 2.5 to 4:100; calcining at 450 to 550° C. to obtain an intermediate; (3) placing the intermediate in 100 to 500 parts by weight of a polyaluminium chloride aqueous solution, with the ratio of polyaluminium chloride to water being 1:8 to 15; immersing and drying to obtain a catalyst.

2. The preparation method according to claim 1, characterized in that: The aluminum oxide precursor includes pseudo-boehmite and boehmite; the zirconium oxide precursor includes zirconium oxysulfate, zirconium oxychloride, zirconium nitrate and zirconium oxyoxalate.

3. The preparation method according to claim 1, characterized in that: The aluminum salt includes one or more of pseudo-boehmite, polyaluminum chloride, tetrahydroxyaluminum, aluminum sol, aluminum trichloride, and aluminum sulfate; the zirconium salt includes one or more of tetrachloroaluminum zirconium, zirconyl sulfate, zirconium nitrate, and zirconium oxychloride.

4. The preparation method according to claim 1, characterized in that: The organic polymer material includes one or more of methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, polyvinyl alcohol and polyethylene glycol.

5. The preparation method according to claim 1, characterized in that: The soluble platinum salt includes one or more of chloroplatinic acid, platinum sulfate, and platinum nitrate.

6. The preparation method according to claim 1, characterized in that: The soluble yttrium salt includes one or more of yttrium nitrate, yttrium chloride, and yttrium oxalate.

7. The preparation method according to claim 1, characterized in that: It includes one of the following: A. 1000 parts of pseudo-boehmite, 100 parts of polyaluminium chloride, 30 parts of methyl cellulose and 300 parts of 35% nitric acid aqueous solution are kneaded, extruded into a strip carrier, dried and calcined at 550° C. to obtain a catalyst carrier; 0.63 parts of chloroplatinic acid and 3.09 parts of yttrium nitrate are dissolved in 150 parts of water, 98.7 parts of the catalyst carrier is impregnated therein, dried, calcined at 500°C, the calcined catalyst intermediate is placed in a polyaluminum chloride aqueous solution, polyaluminum chloride: water = 1:12, impregnated, dried, and the catalyst of the present invention is obtained; B. 500 parts of pseudo-boehmite, 500 parts of zirconyl sulfate, 100 parts of aluminum zirconium tetrachloride, 50 parts of methyl cellulose and 200 parts of 35% nitric acid aqueous solution are kneaded, extruded into a strip carrier, dried and calcined at 550°C to obtain a catalyst carrier; 0.63 parts of chloroplatinic acid and 3.09 parts of yttrium nitrate are dissolved in 150g of water, 98.7 parts of the carrier are impregnated therein, dried and calcined at 500°C, and the calcined catalyst intermediate is placed in a polyaluminum chloride aqueous solution, polyaluminum chloride: water = 1:10, impregnated and dried to obtain a catalyst.

8. A catalyst for isomerization of light normal alkanes, characterized in that: The invention comprises an aluminum oxide or / and zirconium oxide carrier, aluminum oxide or zirconium oxide, platinum, yttrium and polyaluminum chloride loaded in the carrier, wherein the mass percentage of platinum is 0.2-0.5%, the mass percentage of yttrium is 0.8-1.2%, the mass percentage of chlorine is 4-6%, and the specific surface area is 180-230m 2 / g, strength is 80~110N / cm.

9. A method for isomerizing light normal alkanes, characterized in that: The catalyst according to claim 8 is used for the isomerization reaction of light normal paraffins.

10. The method according to claim 9, characterized in that The light normal alkane is selected from one or more of normal butane, normal pentane and normal hexane.